A chimeric recombinant crustacean hyperglycemic hormone from Litopenaeus schmitti (Burkenroad) obtained as C‐terminus fusion protein boost hemolymph glucose concentration in Litopenaeus vannamei (Boone). Issue 7 (13th March 2012) - Morera, Yuliet; Lugo, Juana Maria; Ramos, Laida; Rodríguez‐Ramos, Tania; Huberman, Alberto; Estrada, Mario Pablo
Abstract To date, no hormonal treatments are available for control of shrimp reproduction and only eyestalk ablation is of practical use. The crustacean hyperglycemic hormone (CHH) is the most abundant neuropeptide of the eyestalk CHH family. It plays an important role in the regulation of hemolymph glucose levels, as its principal function, but it is also implicated in additional physiological processes such as moulting and reproduction. In the present study, the cDNA encoding Litopenaeus schmitti (Burkenroad) mature CHH was cloned into the Escherichia coli pTYB2 expression vector. Using this strategy we have obtained, for the first time, the recombinant CHH from L. schmitti with its C‐terminus fused to an intein tag. The expected fused protein of about 63 KDa was expressed in E. coli forming inclusion bodies. It was purified in a soluble form by electroelution following molecular size fractionation in sodium dodecil sulphate polyacrylamide gel electrophoresis. The ability of the chimeric CHH protein to elevate glucose levels in the hemolymph of the eyestalk‐ablated Litopenaeus vannamei (Boone) shrimps indicates that its biological activity as hyperglycemic protein is preserved. The results provide an alternative tool to obtain soluble recombinant proteins from the CHH family of neuropeptides to get a better understanding of shrimp endocrinology.